Gender-based violence: perspectives form Africa the middle east and India - Djamba, Yanyi K; Kimuna, Sitawa R (Switzerland: Springer, 2015)
This book offers new perspectives on gender-based violence in three regions where the subject has been taboo in everyday discourse often due to patriarchal cultural norms that limit women$1 (Bs autonomy. The contributions to this book provide rare insight into not only the levels and the socio-demographic determinants of domestic violence, but topics ranging from men$1 (Bs attitudes toward wife beating; domestic violence-related adolescent deaths, and women$1 (Bs health problems due to sexual and physical abuse. With a comprehensive introduction that provides a comparative international research framework for discussing gender-based violence in these three unique regions, this volume provides a key basis for understanding gender-based violence on a more global level.s
Part 1. Gender-based violence: perspectives from Africa -- 1. Socio-demographic factors associated with men's attitudes toward wife beating in Ethiopia -- 2. First intimate physical violence and fertility in Cameroon -- 3. Violence against young females in South Africa: an analysis of the current prevalence and previous levels of youth mortality 1997-2009 -- 4. Exploring the linkages between spousal violence and HIV in five sub-Saharan African countries -- Part 2. Gender-based violence: perspectives from the Middle East -- 5. Consanguineous marriage: protective or risk factr for intimate partner violence -- 6. Women and health in refugee settings: the case of displaced Syrian women in Lebanon -- 7. Gender dynamics in Palestinian society: domestic and political violence -- Part 3. Gender-based violence: perspectives from India -- 8. Examining nonconsensual sex and risk of reproductive tract infections and sexually transmitted infections among young married women in India -- Questioning gender norms to promote sexual reproductive health among early adolescents: evidence from a school program in MUmbai India -- 10. Transmission of intergenerational spousal violence against women in India
Includes bibliographical references and index
Keywords: Gender-Based Violence; Domestic Violence -- Egypt; Sexual Abuse